Evaluation of Health Care Providers’ Knowledge about Health Restoration for Adults with Physical Disability in Diyala City - Marwa Laith Muhammad, Hala Saadi Abdel Wahed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Adults with disabilities are three times more likely than adults without disabilities to suffer from heart disease, stroke, diabetes, or cancer. Despite the fact that physical activity can help minimize the impact of many chronic conditions, approximately half of persons with disabilities do not participate in physical activity in their spare time. Caregivers' knowledge plays an important role in such people's health rehabilitation. Therefore, thus aimed to assess health care providers knowledge about physical activity promotion for disabled adults. Material and Methods: A convenience sample of 47 health care providers was recruited using a non-probability sampling approach in Diyala Hospitals for a descriptive cross-sectional study. The questionnaire's dependability was established through a pilot research, and it was subsequently presented to experts for validation. The total number of items in the questionnaire for knowledge related to health restoration was 13. The data was acquired using a self-reporting method and evaluated using descriptive and inferential statistical data analysis techniques. RESULTS: The study's findings revealed that the majority of respondents were young male caretakers. According to the study's findings, 48.9 percent of caregivers had insufficient understanding about how to promote physical exercise. There were differences in knowledge with regards health restoration and caregivers gender (p=0.059), years of experience (p=0.001), job description (p=0.001) and training courses (p=0.001). Conclusions: The study concludes that the knowledge in terms of health restoration for disabled adults, health care providers expressed a poor level due to influencing factors such as diploma graduated and nurses specialist is significantly associated poor knowledge. The Directorate of Health needs to adopt guidelines related to the international standard in the management of disability and to rely on specializations from those who have a high level of education in caring for the disabled.